Linda do Rosário: A Jungian Reading - Sanmartin, Stela Maris; Neiva, Simone (Revista do Colóquio, 2025)
This article proposes a symbolic analysis of Adriana Varejão’s work Linda do Rosário (2004) in light of Carl Gustav Jung’s analytical psychology. The archetypes of the shadow and anima/animus, as well as the concepts of active imagination and individuation, will be used to explore how the work provokes the viewer to confront repressed contents of the individual and collective psyche. Through this approach, the aim is to understand the transformative power of art as a catalyst for psychological processes.